Moss, Vietnam - An American Ordeal, Kimball Ed., To Reason Why - A Debate About The Cause Of U.S. Involvement In The Vietnam War - Burdick, Frank (Teaching History: A Journal of Methods, 1992)
George Moss’s Vietnam: An American Ordeal is the most thorough, up-to-date, and analytical account of the Vietnam War since George Herring’s classic America’s Longest War. Setting out to provide an "objective" account of the long agony of Vietnam, Moss has made splendid use of a vast variety of sources to provide a balanced and comprehensive history of the American experience.